An ectodermal dysplasia patient treated with a small diameter implant supporting a single crown - Mascolo A (Clinical, Cosmetic and Investigational Dentistry, 2018)
Andrea Mascolo,1 Elio Boschetti,1 Dennis Flanagan2 1European Institute for Medical Studies, H.E.I. Graduate School, Malta; 2Private Practice, Willimantic, CT, USA Abstract: Ectodermal dysplasia (EDD) is a developmental disorder that affects the skin, hair, and teeth among other organs generated in the ectoderm. Dental implants have been used to successfully treat partial edentulism in EDD patients, but the success rate is much lower for these patients. The report herein is a successful case of a single mini, small diameter, implant used to support a single crown of a mandibular right second premolar. A review of implant treatment in EDD patients is included. Keywords: dental implant, mini implant, occlusal, load, osseointegration